SISTEM INFORMASI AKADEMIK SMA NEGERI 1 SIMPANG EMPAT KABUPATEN KARO - Devi Oliviani Br Sitepu; Parasian Silitonga (PUBLIKASI ILMIAH TEKNOLOGI INFORMASI NEUMANN (PITIN), 2018)
In current technological developments, fast and easy information is needed as a means of information that can manage academic information systems quickly and accurately. The design and manufacture of this website aims to facilitate the processing of academic data and can be a medium of information for all students, parents and teachers who have difficulty in obtaining data about the academic system. The facilities contained in this application in the form of providing data such as the homepage, profiles, contacts, news, student data, teacher data, classes, student guardians, subjects that are useful for the continuity of student learning. In the process of making a web consisting of apache server, PHP and MySQL, PHP, Apache as a web server, MySQL as a database.